(untitled) (Revista de Ciências Agroveterinárias, 2019)
Brassica cabbage (Brassica oleracea var. Acephala L.) belongs to the Brassicaceae family and several studies have shown the variations in gas exchange between plants and the atmosphere, due to practices or treatments applied to agricultural crops, with consequent stress and negative reflexes on the metabolic processes of plants. In addition to being an option for those seeking organic production, liquid humus is an economic and efficient strategy with numerous benefits, both economic and agronomic. In this sense, the objective was to evaluate some physiological and morphological variables in cabbage plants, with concentrations of liquid humus. The experiment was carried out in a protected environment in the experimental area of Horticulture and Biological Control, belonging to UNIOESTE, in the city of Marechal Cândido Rondon, PR. The treatments consisted of five doses of liquid humus (0, 5, 10, 15, and 20%). Fertilization with liquid humus significantly influenced liquid photosynthesis, internal CO2 concentration and water use efficiency. Dry masses of stem, leaf, and total were not influenced by the treatments. The number of leaves per plant and the leaf area were affected by the concentrations of liquid humus. Although the variables transpiration and stomatal conductance did not present significant difference, the other parameters presented positive results in relation to the increase of liquid humus. However, the higher number of leaves per plant did not influence the assimilation rate of CO2.